Usage of foamed lightweight concrete arch tile as permanent formwork for upper floor slab - Rosnani, Deraman (2015)
In Malaysia nowadays, the method of construction in our country is left behind compared to other countries. The contractors and developers are still struggling in catching up with the current rate of development where the type of construction which is conventional method is still being used. Although conventional method is customary practice, it has weakness that cannot deny such as material and high labour cost, especially waste material at construction site. Therefore, permanent formwork is chosen to overcome these deficiencies. Concisely, the usage of permanent formwork brings the advantages better than conventional method in terms of safety features, effectiveness of the function, lighter and productivity. Hence, this research is carried out to determine the maximum load that can carry by the arch tile where nine sets of arch tile were tested on 7,14 and 28 days. The compressive strength test also tested to the cube. Based on the testing, it shows that the 75mm of arch tile height resist the maximum load until cracking and the compressive strength is increase parallel with time